Dynamic Modeling of Tannase Production from Bacillus cereus: A Framework Simulation based on Fed Batch Strategy (2021)
Tannase enzyme is a metabolite of great interest in the industry. Typical examples of its use can be found in wines and beer production, beverage and juice fruits clarification and leather production. However, tannase production on an industrial scale is limited to the operation batch mode. For this reason, its production is low and severe limitations take the place of being carried on a large scale. To improve production, this research proposes an operation strategy based on Fed-batch mode. The kinetic constants were taken from the literature to simulate trends obtained through a Feed-batch mode of operation. One of the most important findings of this research focuses on increasing tannase production with found values of 0.380 U/g. The latter indicates that tannase production could be almost twice the concentration obtained with the traditional batch mode (0.1900 U/g). Results obtained in this research may be promising for the enzyme production industry. Using computational techniques, it is possible to identify an improvement without investing in excessive experimentation and resources.